Length Change Pattern of the Medial Structures of the Knee and Related Reconstructions. Issue 5 (28th May 2020) - Kittl, Christoph; Olbrich, Arne; Raschke, Michael J.; Domnick, Christoph; Glasbrenner, Johannes; Herbst, Elmar; Frank, Andre; Herbort, Mirco
Aims and Objectives: Chronic medial instability presents a severe problem both for the patient and the surgeon, and may result into anterior cruciate ligament graft failure in a combined anteromedial instability. Thus, reconstructions have been developed to conquer this problem. However, these are not capable of mimicking the flat anatomy of the medial structures of the knee. The goal of the present study was to examine the length change patterns of the native medial structures of the knee and their related reconstructions. It was hypothesised that the different portions of the medial collateral ligament present different length change patterns, which cannot be imitated by current reconstructions. Materials and Methods: Eight cadaveric knees were dissected of skin and subcutaneous fat. The satorius fascia was removed to get a clear vision of the medial structures. The knee was then mounted in a rig and the quadriceps muscle and the iliotibial tract were loaded, using cables and hanging weights, according to its fiber orientations and cross-sections. Threads attached to three tibial pins at the anterior/middle/posterior portion of the medial collateral ligament (MCL) were then guided to three femoral eyelets at the anterior/middle/posterior portion of the femoral MCL insertion and analogous with the tibial/femoral posterior oblique ligament (POL) insertion. A tibial pin was also put at the semitendinosus insertion to imitate the Lind reconstruction. Between 0-120 degree knee flexion, the distances between each possible tibiofemoral combination were measured using a linea variable differential transformer (LVDT). Statistical analysis was performed using two way repeated measurements ANOVA. Results: The anterior MCL showed an initial slackening (2%) until 20° flexion, followed by a tightening (5%) towards deep flexion (120°), meaning that it is tight in flexion. The posterior MCL also showed an initial slackening (4%) until 20° of flexion. However, then followed by an isometric area (20-80°) and a further slackening (8%) towards deep flexion (120°), meaning that it is tight in extension. The three portions of the POL showed a linear slackening between 0-120° (25%). The middle MCL showed a sine wave behaviour, slackening from 0- 60° (3%) and tightening between 60-100° (1%). This behaviour was similar in the Lind and Robinson reconstruction, which were the most isometric tibiofemoral combinations (total strain range: 5, 3 ± 2, 1). The native POL length changes showed the most non-isometric behaviour resulting into a total strain range of 28, 8 ± 6, 2, which was significantly different from the native MCL and MCL reconstructions (p< .001) Conclusion: The anterior, middle, and posterior parts of the MCL showed different length change patterns. The anterior part tightened in flexion, whereas the posterior part tightened in extension. This behavior could not be reproduced by the current reconstructions, such as the Lind and Robinson procedure, which only could imitate the middle portion of the native MCL.